Paraganglioma of the Spermatic Cord: Case Report and Review of the Literature - G. Garaffa; A. Muneer; A. Abdel Raheem; A. Freeman; D. J. Ralph; S. Minhas; R. W. Rees (The Scientific World Journal)
Paragangliomas rarely involve the genitourinary tract. We present a case of a paraganglioma arising from the spermatic cord and review the literature on the topic.